Analisis Dampak Job Hopping, Budaya Organisasi, Dan Gaya Kepemimpinan Terhadap Kepuasan Kerja Pegawai Dengan Perkembangan Karir Sebagai Variabel Mediasi Pada BKPSDM Kota Malang - Li Izzati Maulidina; Nurhidayah Nurhidayah; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study analyzes the influence of job hopping, organizational culture, and leadership style on employee job satisfaction, with career development as a mediating variable at the Malang City Human Resources Development Agency (BKPSDM). Civil servant job satisfaction is crucial for improving the quality of public services in local government agencies. The study employed a quantitative explanatory approach with a population of Malang City Civil Servant Agency (BKPSDM) employees. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results showed that job hopping had a positive and significant effect on job satisfaction. However, organizational culture and leadership style did not have a significant direct effect on job satisfaction. Organizational culture and leadership style had a significant positive effect on career development, while job hopping had no effect. Career development did not significantly influence job satisfaction and did not mediate the relationship between the three independent variables and job satisfaction (no mediation in all paths). These findings indicate that in the context of a rigid civil servant bureaucracy, job satisfaction is more directly influenced by job stability and internal job mobility than by career development. The implication is that the BKPSDM needs to optimize internal job hopping and strengthen leadership to increase employee satisfaction. Keywords: Job Hopping, Organizational Culture, Leadership Style, Career Development, Job Satisfaction.